Raising Critical Thinkers: Critical Thinking Skills in Secondary Social Studies Curricula in Turkey - (:unkn) unknown (KAMLA-RAJ ENTERPRISES, 2015)
Developing critical thinking skills and raising critical thinkers is considered amongst the purposes of education, The aim of the present study was to investigate to what extent critical thinking skills were reflected in the attainments of the secondary social studies curricula in Turkey. Attainments of three secondary curricula in the field of social studies were examined in the study, which has a qualitative case study design, and the data was obtained from document analysis. The results demonstrated that none of the examined three curricula were found to establish a direct relationship between attainments and critical thinking skills, However, it was possible to find the attainments relevant to critical thinking skills when they were examined in detail. Attainments that were relevant to critical thinking skills were mostly found in the Geography curriculum (66.66%), followed by History (31.89%) and Democracy and Human Rights curriculum (16.66%) respectively,
Keywords: Critical Thinking; Education and Culture; Individual and Thinking; Secondary Social Studies Curricula; TEACHING CRITICAL THINKING; GEOGRAPHY